Motion and Rest from a Chinese Buddhist Perspective - Sluyter, Caroline (Stance: an international undergraduate philosophy journal, 2019)
This paper focuses on Seng-Chao’s conception of motion and rest as two different ways to see the same phenomenon and the effect that this has on his understanding of ideas such as impermanence. I point out the parallels that can be made between motion and rest and samsara and nirvana and I argue that a strong Taoist background helps Seng-Chao clarify Indian ideas and make even deeper claims about the true nature of reality.